Application of Piezoelectric Materials in Smart Roads and MEMS, PMPG Power Generation with Transverse Mode Thin Film PZT - Aqsa Abbasi (Institute of Advanced Engineering and Science, 2013)
Due to the increase in electricity energy consumption and the fact that about 90 % of fuels being used now are co2 pollutant and the crisis has been caused by greenhouse gases have made moving toward renewable energies unavoidable. At present, considering electricity crisis in Pakistan, although only 46% of the population of Pakistan have the facility of electricity and the remaining are still living in darkness but still we face a major power crisis. Modern technology needs a huge amount of electrical power for its various operations. Electricity production is the single largest source of pollution in the whole world. In this paper, we have presented and reviewed a method to produce pollution free electricity by some techniques like Piezoelectric effect in some specisl crystal such as pyroelectric crystal, Quartz crystal, PZT and using them in piezoelectric roads, as congestion on roads is becoming inevitable with the fancy of masses towards personal transportation systems for their growing mobility. Accordingly, it is an object of the present invention to provide a method of electrical power generation that does not negatively impact the environment.DOI:http://dx.doi.org/10.11591/ijece.v3i6.4588